Utility of hemoglobin A1c to screen for impaired glucose tolerance - Edy K. Ginting; Aditiawati Aditiawati; Irfanuddin Irfanuddin (Paediatrica Indonesiana, 2014)
Background Childhood obesity is associated with an increasedlikelihood for having impaired glucose tolerance, dyslipidemia,and diabetes. Hemoglobin Ale (HbAl c) h as emerged as arecommended diagnostic tool for identifying diabetes and personsat risk for the disease. This recommendation was based on datain adults, showing the relationship between HbAl C and thefuture development of diabetes . However, studies in the pediatricpopulation have been limited and no stan dard values of HbAlclevels in children have been established.Objective To evaluate HbAlc as a test for impaired glucosetolerance in obese children and adolescents and to identify theoptimal HbAlc thresh old level (cut off poin t).Methods We studied 65 obese and 4 overweight children (BMI 2::+ 2 SD for age and gender) aged 10-15 years in Palembang. Allsubjects underwent HbAlc and oral glucose tolerance tests.Results Nineteen out of 69 subjects (28%) had impaired glucosetolerance. Based on the receiver operating characteristic curve,the optimal cut off point of HbAlc related to impaired glucosetolerance as diagnosed by oral glucose tolerance test was found tobe 5.25%, with 63% sensitivity and 64% specificity, 40% positivepredictive value, and 82% negative predictive value. The areaunder the receiver operating ch aracteristic curve was O .68 7(95%CI 0.541-0.833; P < 0.00 1).Conclusion A HbAlc cut off value of 5.25% may be used as ascreening tool to identify children and adolescents with impairedglucose tolerance.